Optimal International Agreement and Restriction on Domestic Efficiency - LEE, Gea M. (Institutional Knowledge at Singapore Management University, 2016)
The WTO's strict treatment of domestic subsidies has not been well received in the existing literature. An essential reason is that the consequent restriction on domestic efficiency is hardly compatible with the existing theory of government intervention under which the primary objective of using domestic subsidies, domestic efficiency, is not sacrificed for another objective. We develop a trade-agreement model in which the magnitude of a legitimate domestic subsidy with which to address a production externality is private information. We find that an optimal agreement substantially restricts domestic efficiency for the international objective of expanding market access.